2014
DOI: 10.1016/j.schres.2013.11.015
|View full text |Cite
|
Sign up to set email alerts
|

White matter abnormalities in 22q11.2 deletion syndrome: Preliminary associations with the Nogo-66 receptor gene and symptoms of psychosis

Abstract: Background This study utilized diffusion tensor imaging (DTI) to analyze white matter tractography in anterior limb of the internal capsule (ALIC), fornix, and uncinate fasciculus (UF) of individuals with 22q11.2 Deletion Syndrome and controls. Aberrations in these tracts have been previously associated with schizophrenia. With up to 25% of individuals with 22q11.2DS developing schizophrenia in adulthood, we hypothesized reduction in structural integrity of these tracts, including an association with prodromal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 68 publications
7
40
1
Order By: Relevance
“…DTI studies on 22q11.2DS are in agreement with this finding, showing a genetic effect localized in specific CC regions [21,22] . Our result, however, is inconsistent with that of Perlstein et al [28] , who investigated the effect of the same SNP, rs701428, and reported that the G allele is associated with reduced RD. The discrepancy might be due to the difference in the white matter regions reported to be associated with the allelic variation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…DTI studies on 22q11.2DS are in agreement with this finding, showing a genetic effect localized in specific CC regions [21,22] . Our result, however, is inconsistent with that of Perlstein et al [28] , who investigated the effect of the same SNP, rs701428, and reported that the G allele is associated with reduced RD. The discrepancy might be due to the difference in the white matter regions reported to be associated with the allelic variation.…”
Section: Discussioncontrasting
confidence: 99%
“…An association between allelic variations of this SNP and diffusion tensor imaging (DTI) metrics of the white matter tract has been reported in 22q11.2DS patients [28] . To examine the roles of NgR1 in CC formation, we investigated a possible association between NgR1 genetic variation and CC structure in healthy participants, using structural magnetic resonance imaging (MRI) and DTI.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings of microscopic structural alterations in axonal branching in conjunction with current and previous finding of altered synaptic transmission and plasticity in cortical synapses of Df(16)A +/− mice (Fenelon et al, 2011, 2013) offers a plausible neural substrate that may underlie the mesoscopic scale neuroimaging findings. In addition, there is accumulating data linking neuroimaging measures with the psychosis phenotype in 22q11.2 deletion carriers providing support for the notion that structural and functional dysconnectivity is particularly relevant to the psychosis phenotype in 22q11DS (Kates et al, 2014; Perlstein et al, 2014; Jalbrzikowski M et al 2014; Ottet et al, 2013b). In that respect, our data suggests that the altered axonal connectivity that emerge as a result of deficits in neuronal palmitoylation contribute to the psychiatric deficits associated with the 22q11 deletion.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were between the ages of 16 and 20 years and were recruited at SUNY Upstate Medical University, Syracuse, NY. The same subjects’ images were used in two tractography studies of white matter microstructure (Perlstein et al 2014; Kates et al 2015) and in an atlas-based study of white matter microstructure on a subset of study participants, i.e., 48 out of 97 study subjects (Radoeva et al 2012). For participants with 22q11DS, deletion of the chromosomal region 22q11.2 was confirmed by Fluorescent-In-Situ-Hybridization (FISH).…”
Section: Methodsmentioning
confidence: 99%
“…The syndrome is characterized by a copy number variation (CNV), namely a deletion of over 40 genes on one copy of chromosome 22 (Karayiorgou et al 1995; Murphy et al 1999). White matter abnormalities are present in 22q11DS and include reduced FA in interhemispheric connections, as well as across the frontal, parietal , temporal and limbic regions (Villalon-Reina et al 2013; Sundram et al 2010; Simon et al 2005; Barnea-Goraly et al 2003; Kates et al 2015; Perlstein et al 2014; Deng et al 2015; da Silva Alves et al 2011; Jalbrzikowski et al 2014; Radoeva et al 2012; Barnea-Goraly et al 2005) . Abnormalities in maturational trajectories of white matter development (based on cross-sectional data) have also been reported in children and young adults with 22q11DS (Jalbrzikowski et al 2014).…”
Section: Introductionmentioning
confidence: 99%